Prevention of Corruption-Related Criminal Offences in the State Penitentiary Service of Ukraine (Bulletin of Kharkiv National University of Internal Affairs, 2025)
The article examines the problem of preventing corruption-related crime in the State Penitentiary Service of Ukraine. It is noted that corruption-related crime has its own determinants of emergence and existence. It is stated that corruption offences in the state in general and in the penitentiary system in particular are a threat to the existence of society, a danger to its state and political organisation, i.e. to the existence of statehood. The main principles of anti-corruption policy, defined by the Anti-Corruption Strategy for 2021–2025, are considered.It is noted that today society has a fairly active demand for information on the state of corruption, the identification of the determinants of its commission, and the need to develop effective mechanisms to prevent and counteract this socially negative phenomenon in order to ensure the proper trust of citizens in the authorities and the law enforcement system. It is noted that the problem of corruption has been exacerbated by the introduction of martial law in connection with Russia's war against Ukraine. It is proved that corruption undermines trust in state institutions, hinders economic development and demoralises society. The existence of corruption in the State Penitentiary Service of Ukraine poses an increased public danger, as corruption offences violate the rights and freedoms of citizens who are isolated from society.Based on research into the legal and social nature of corruption, the concept of “corruption prevention in the State Penitentiary Service of Ukraine” has been defined as a set of systematic, interrelated and coordinated educational, legal and socio-economic measures whose main goal is to eliminate the determinants of corruption among officials of the State Penitentiary Service of Ukraine, as well as to create a social environment in which corruption is risky and morally unacceptable.